Realizing Room‐Temperature Resonant Tunnel Magnetoresistance in Cr/Fe/MgAl2O4 Quasi‐Quantum Well Structures. Issue 20 (10th August 2019) - Xiang, Qingyi; Sukegawa, Hiroaki; Belmoubarik, Mohamed; Al‐Mahdawi, Muftah; Scheike, Thomas; Kasai, Shinya; Miura, Yoshio; Mitani, Seiji
Abstract: The quantum well (QW) realizes new functionalities due to the discrete electronic energy levels formed in the well‐shaped potential. Magnetic tunnel junctions (MTJs) combined with a quasi‐QW structure of Cr/ultrathin‐Fe/MgAl2 O4 (001)/Fe, in which the Cr quasi‐barrier layer confines Δ 1 up‐spin electrons to the Fe well, are prepared with perfectly lattice‐matched interfaces and atomic layer number control. Resonant peaks are clearly observed in the differential conductance of the MTJs due to the formation of QWs. Furthermore, enhanced tunnel magnetoresistance (TMR) peaks at the resonant bias voltages are realized for the MTJs at room temperature, i.e., it is observed that TMR ratios at specific and even high bias‐voltages ( V bias ) are larger than zero‐bias TMR ratios for the MTJs with odd Fe atomic layers, in contrast to the earlier experimental studies. In addition, a new finding in this study is unique sign changes in the temperature coefficient of resistance (TCR) depending on the Fe thickness and V bias, which is interpreted as a signature of the QW formation of Δ1 symmetry electronic states. The present study suggests that the spin‐dependent resonant tunneling via the QWs formed in Cr/ultrathin‐Fe/MgAl2 O4 /Fe structures should open a new pathway to achieve a large TMR at practically high V bias . Abstract : Inside Cr/ultrathin‐Fe/MgAl2 O4 /Fe‐based magnetic tunnel junctions, quantum well (QW) states are established within a precisely thickness‐controlled ultrathin Fe layer. Via the QW states, the tunnel magnetoresistance (TMR) is strongly modulated at room temperature. For odd Fe atomic layer cases, the resonance appears at a high bias voltage, where the TMR is even higher than the value at zero bias.